Long‐term English learners: Current research, policy, and practice. Issue 1 (5th May 2019) - Clark‐Gareca, Beth; Short, Deborah; Lukes, Marguerite; Sharp‐Ross, Mary
Abstract : Given that English learners (ELs) comprise one of the fastest growing populations in PK–12 environments, long‐term English learners (LTELs) form one subgroup that provokes particular concern. This article explores current understandings of the LTEL designation and discusses diagnostic processes and assessment tools for determining English language proficiency. Complexities of referring ELs/LTELs for special education are then probed with regard to drawing the careful line between language proficiency processes and special education needs. Finally, the authors present possible interventions for LTELs, including the Internationals Network as a large‐scale intervention model, followed by smaller scale interventions made on behalf of LTELs in existing schools. The article concludes with strategies and suggestions toward better outcomes for LTELs in school.